KNOWLEDGE-BASED VIEW, INTERNATIONAL STRATEGY, AND INNOVATION: EFFECTS ON FIRM PERFORMANCE IN MSME - Moron, Maria Selvi; Wisnu Yuwono; Erilia Kesumahati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study examines how knowledge-based resources influence MSME performance in Batam’s food and beverage sector by integrating the Knowledge-Based View and internationalization theory. We propose that digitalization, knowledge processes, IT infrastructure, and risk management affect firm performance directly and indirectly through international strategy, while innovation functions as a potential moderator. A cross-sectional survey of 200 owners and managers was analyzed using partial least squares structural equation modeling. Results indicate that all four KBV components exert significant positive direct effects on international strategy and on firm performance. International strategy partially mediates the relationships between KBV resources and performance. Innovation, operationalized primarily as process and incremental innovation, did not moderate the examined relationships. The structural model explains 61.5 percent of variance in firm performance and 30 percent in international strategy and meets fit criteria with an SRMR of 0.067. These findings extend KBV to MSMEs in a developing-market context by demonstrating that internal knowledge and technological capabilities, when orchestrated through international strategy, enhance firm performance. Practically, managers should prioritize knowledge management, targeted digital investments, and basic risk controls, while policymakers should combine innovation support with capacity-building programs to convert innovation into international performance gains. Future studies should adopt longitudinal and cross-country designs.